The Relationship between Mother's Level of Knowledge About MP-ASI and EventsStunting among toddlers in Jenggrik Village, Kedawung District, Sragen Regency - Afiffah Aulia Rohmah; Syefira Ayudia Johar; Fiqi Nurbaya (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
Sragen Regency is one of the districts with a prevalence ratestunting which is quite high. Numberstunting in Sragen there has been an increase from 4,353 children in 2021 to 5,085 children in 2022.The aim of this research was to determine the relationship between the mother's level of knowledge about MP-ASI and the incidentstunting I n toddlers in Jenggrik Village. This type of research is quantitative by design Case Control. The population and sample for this study were 49 cases and 49 control groups with toddler mothers/caretakers as respondents. TechniqueSampling using techniquesTotal Sampling. This research instrument uses a questionnaire and is processed usingsoftware SPSS through analysischi square95% confidence level (a = 5%). The results of the univariate analysis of the level of knowledge of mothers in the low knowledge case group were more dominant at 30 (61.2%), while the high knowledge control group was more dominant at 48 (98.0%). Results of univariate analysis of eventsstunting case group experiencedstunting (100%), while the control group experienced no eventsstunting (100%). The results of bivariate analysis show There is a relationship between the mother's level of knowledge about MPASI and the incident stunting to Toddlers in Jenggrik Village with valuesp-value 0,000 < 0,05. Recommended for mothers toddlers to be more active in seeking information about children's growth and development, the impacts they have, as well as knowledge about providing MP-ASI, either through health education, social media, radio, newspapers, etc.